2016
DOI: 10.4103/0366-6999.185867
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of c-Jun N-terminal Kinase Signaling Pathway Alleviates Lipopolysaccharide-induced Acute Respiratory Distress Syndrome in Rats

Abstract: Background:An acute respiratory distress syndrome (ARDS) is still one of the major challenges in critically ill patients. This study aimed to investigate the effect of inhibiting c-Jun N-terminal kinase (JNK) on ARDS in a lipopolysaccharide (LPS)-induced ARDS rat model.Methods:Thirty-six rats were randomized into three groups: control, LPS, and LPS + JNK inhibitor. Rats were sacrificed 8 h after LPS treatment. The lung edema was observed by measuring the wet-to-dry weight (W/D) ratio of the lung. The severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…JNK inhibitors not only inhibit the JNK pathway but also reduce the production of oxidative stress metabolites. [ 51 ] Further in vivo studies in rats demonstrated that SP600125, a JNK inhibitor, thinned the theca cell layer, reduced interstitial collagen deposition, and attenuated inflammation. As a result, ovarian fibrosis was apparently diminished on some level.…”
Section: R Elationship Between O Varian mentioning
confidence: 99%
“…JNK inhibitors not only inhibit the JNK pathway but also reduce the production of oxidative stress metabolites. [ 51 ] Further in vivo studies in rats demonstrated that SP600125, a JNK inhibitor, thinned the theca cell layer, reduced interstitial collagen deposition, and attenuated inflammation. As a result, ovarian fibrosis was apparently diminished on some level.…”
Section: R Elationship Between O Varian mentioning
confidence: 99%
“…[21] Manipulation of JNK/MAPK pathway could be a potential therapeutic target for acute respiratory distress syndrome (ARDS) in the context of suppressing inflammation. [22] Western blotting results showed that, like GSH, BV treatment decreased the phosphorylation of JNK which was greatly induced in the I/R group ( P < 0.01) [Figure 3]. …”
Section: Resultsmentioning
confidence: 99%
“…ARDS, the most severe form of ALI, 35 37 is a clinical syndrome of noncardiogenic pulmonary edema. 38 40 ARDS is characterized by an excessive inflammatory response, 41 43 damage to both alveolar epithelial 38 , 40 , 41 and vascular endothelial 39 , 44 , 45 cells, the subsequent breakdown of the alveolar-capillary barrier integrity, 38 , 42 , 46 impaired AFC, 40 , 41 , 45 excessive interstitial and parenchymal neutrophil migration, 38 , 43 , 45 and activation of alveolar macrophages, platelets, and pro-coagulant processes. 42 , 47 , 48 This may result in diffuse alveolar damage, 42 , 49 pulmonary fibrosis, 37 , 50 and impaired gas exchange, 42 , 51 leading to (refractory) hypoxemia 35 , 38 , 42 and possibly organ dysfunction.…”
Section: Covid-19mentioning
confidence: 99%
“… 42 , 47 , 48 This may result in diffuse alveolar damage, 42 , 49 pulmonary fibrosis, 37 , 50 and impaired gas exchange, 42 , 51 leading to (refractory) hypoxemia 35 , 38 , 42 and possibly organ dysfunction. 40 , 47 , 52 …”
Section: Covid-19mentioning
confidence: 99%
See 1 more Smart Citation